Protein-protein recognition in biological systems exhibiting highly-conserved tertiary structure: cytochrome P450 - Johnson, E; Eachan Oliver Daniel Johnson (2013)
Protein tertiary structure is more conserved than amino acid sequence, leading to a diverse range of functions observed in the same fold. Despite < 20 % overall sequence identity, cytochromes P450 all have the same fold. Bacterial Class I P450s receive electrons from a highly specific, often unidentified, ferredoxin, in which case the hemoprotein is termed “orphaned”. CYP199A2, a Class I P450, accepts electrons from ferredoxins Pux and HaPux. Five orientation-dependent and one orientation-independent DEER measurements on paramagnetic HaPux and spin-labelled CYP199A2 yielded vector restraints, which were applied to building a model of the CYP199A2:HaPux complex in silico. A different binding mode was observed compared to P450cam:Pdx and P450scc:Adx, both recently elucidated by X-ray crystallography. This protocol was also applied to the CYP101D1:Arx complex. The first three measurements indicate that this heterodimer does not have a similar orientation to CYP199A2:HaPux, P450cam:Pdx, or P450scc:Adx. P450cam was fused to putidatredoxin reductase (PdR) to explore the kinetic effects with a view to improving electron transfer to orphan P450s. Heme incorporation of this enzyme depends on linker length. In whole cells, the fusion was more active after longer incubations. In vitro kinetics of the fusion exhibited some co-operativity and enhanced kinetics over the unfused system under steady-state conditions. The putative iron-sulfur biosynthesis ferredoxin PuxB had been engineered by rational mutagenesis to support catalysis by CYP199A2. It was confirmed this arose from improved protein-protein recognition. Engineering of E. coli ferredoxin based on these findings was carried out, resulting in electron-transfer to CYP199A4 from a novel engineered alien ferredoxin.